Anti-Müllerian hormone levels in women with polycystic ovarian syndrome compared with normal women of reproductive age in China. (February 2014) - Tian, Xuanxuan; Ruan, Xiangyan; Mueck, Alfred O.; Wang, Juan; Liu, Shunyu; Yin, Dongmei; Lu, Yongjun; Wu, Hongqin; Zhang, Ying
Abstract Objectives: Aim was to evaluate anti-Müllerian-hormone (AMH) in women with polycystic ovary syndrome (PCOS) comparing with normo-ovulatory women, and to assess for the first time AMH levels across reproductive lifespan in Chinese women. Methods: Within the prospective cross-sectional study in PCOS cases and in normal subjects, AMH and other hormone levels were measured in early follicular phase in five age groups. Additionally ovarian ultrasound parameters were assessed. Results: A total of 437 PCOS patients and 150 normo-ovulatory women matched by age were included. AMH levels were 2- to 3-fold higher in PCOS cases. In both groups AMH decreased with age in a non-linear pattern. In normo-ovulatory women AMH levels were relatively constant from 18 to 25 years and then declined with age. In contrast, AMH in PCOS cases declined with an increasing rate from 18 to 45 years, narrowing the difference in older women. Conclusions: AMH may be a useful parameter to assess the severity and prognosis of PCOS since certain differences exist to normo-ovulatory women. Further studies may improve the understanding of the relationship between AMH levels and age, providing more scientific basis for fertility counselling for both healthy women and PCOS cases.